2016
DOI: 10.18325/jkmr.2016.26.4.117
|View full text |Cite
|
Sign up to set email alerts
|

Fourty One Cases on MRI (Magnetic Resonance Imaging) Change of Hivd of L-Spine Patient Who Have Been Improvement on Megadose Pharmacoacupuncture and Korean Medical Treatments

Abstract: Objectives The purpose of this study is to report the effect of Megadose Pharmacoacupuncture combined with conservative Korean medicine treatment on Herniated InterVertebral Disc (HIVD) of lumbar spine patient diagnosed by Magnetic Resonance Imaging (MRI). Methods This study includes 41 patients whose Lumbar Disc Herniations were by MRIbetween 1st Aprill 2011 and 31th March 2016. All of the patients were treated with Megadose Pharmacoacupuncture combined with Korean medicine treatment. The MRI examination was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Conservative Korean Medicine treatment of HNP is being practiced. In case reports that accompanied large dose pharmacopuncture [13], bee venom [14], and chuna [15] with Korean Medicine treatment, radiological change of the herniated disc was observed. Acupotomy has been shown to decrease pain [3][4][5], but to date there has not been a Korean clinical case reported that has compared radiological evidence of change before and after acupotomy using CT or MRI imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative Korean Medicine treatment of HNP is being practiced. In case reports that accompanied large dose pharmacopuncture [13], bee venom [14], and chuna [15] with Korean Medicine treatment, radiological change of the herniated disc was observed. Acupotomy has been shown to decrease pain [3][4][5], but to date there has not been a Korean clinical case reported that has compared radiological evidence of change before and after acupotomy using CT or MRI imaging.…”
Section: Discussionmentioning
confidence: 99%